2022
DOI: 10.1183/23120541.00643-2021
|View full text |Cite
|
Sign up to set email alerts
|

ERS International Congress 2021: highlights from the Paediatric Assembly

Abstract: This manuscript has recently been accepted for publication in the ERJ Open Research. It is published here in its accepted form prior to copyediting and typesetting by our production team. After these production processes are complete and the authors have approved the resulting proofs, the article will move to the latest issue of the ERJOR online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…The ERS International Congress 2023 showed that advances in paediatric respiratory medicine are rapidly advancing. In line with previous years [ 82 , 83 ], we present a selection of the outstanding sessions on behalf of Assembly 7 (Paediatrics) in order to inform the reader of the latest developments and encourage participation in future ERS activities [ 84 ]. Overall, it has become evident that respiratory health in early life impacts respiratory health in childhood and adulthood, which underlines the need for collaboration among healthcare providers and researchers from different disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…The ERS International Congress 2023 showed that advances in paediatric respiratory medicine are rapidly advancing. In line with previous years [ 82 , 83 ], we present a selection of the outstanding sessions on behalf of Assembly 7 (Paediatrics) in order to inform the reader of the latest developments and encourage participation in future ERS activities [ 84 ]. Overall, it has become evident that respiratory health in early life impacts respiratory health in childhood and adulthood, which underlines the need for collaboration among healthcare providers and researchers from different disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…To make translational science at the ERS more visible, translational tags were introduced to highlight these sessions and to attract the right audience. Previously, congress sessions were tagged as either basic or clinical to indicate the target audience of each session, as can be observed in previous congress highlights articles [40][41][42]. However, sessions that contain a mix of basic and clinical science are encouraged, as is research that is translational in nature.…”
Section: Increasing the Visibility Of Translational Science At The Er...mentioning
confidence: 99%